Fecundity Study and Histological Analysis of the Gonads of the Sea Cucumber Holothuria tubulosa (Echinodermata: Holothuroidea) in the Central Aegean Sea, Greece: Insights into Reproductive Biology - Athina Balatsou; Chrysoula Apostologamvrou; Dimitris Vafidis (Fishes, 2025)
The Atlanto-Mediterranean sea cucumber Holothuria tubulosa is a species of great ecological and commercial importance, making it a primary target for collection in the Mediterranean region. This study investigated the reproductive biology of H. tubulosa (Gmelin, 1793) in a coastal area of the Central Aegean Sea (Eastern Mediterranean) over a one-year period, from June 2021 to May 2022. Monthly sampling was conducted via dives at depths up to 10 m, alongside the recording of environmental and biometric data. Histological analysis revealed a synchronous annual reproductive cycle, with gonadal maturation beginning in April and peak sexual maturity observed in July and August, followed by a single spawning event from August to September. The sex ratio was 1:1.31 (male: female), and the size at first maturity was 255.3 mm. These findings provide essential insights into the reproductive physiology of H. tubulosa and further contribute to the development of sustainable stock management strategies for sea cucumbers in the Hellenic Seas.